ANALISIS KEMAMPUAN MENGINTERPRETASI DAN MENULIS SYAIR SISWA KELAS X SMA KOTA LANGSAPROVINSI ACEH - Habsari Pratiwi, Siti (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract The aim of this study is to investigate the ability of senior high school studentsin Kota Langsa in interpreting and writing syair. This study examines the correlation between interpreting syair as independent variable and writing syairas dependent variable. This study used test as instrument in gathering the required data: test of an essay consisting of dictions and moral values from 10 bait of âSyairPerahuâ and writing test of five stanzas (bait) of syairabout love for parents. 93 students from two schools, SMAN 1 Langsa and SMA CutNyakDien, were selected as sample of the study. The obtained data were analyzed statistically using Pearson Product-Moment. The finding of this study shows that the ability of the student in interpreting is 67.07 and falls into medium. The ability of the student in writingsyair is 52 and falls into poor. After analyzing the two variables using Person Product-Moment, it is obvious that interpreting syairdoes not significantly influence the studentâs writing, since the interpreting syair only influences the writing by 9.5%.Keywords: syair, interpreting, writing, bait,and SyairPerahu.